Fiscal Sustainability Assessment: The case of Thailand: Fiscal Sustainability Assessment: The case of Thailand - asava-vallobh, norabajra; Aroonvisoot, Rom; Yangwiwat, Chonlathit (Journal of Applied Economics and Management Strategy, 2018)
ABSTRACT This paper aims to illustrate various aspects of fiscal sustainability. First, conceptual and literature reviews of fiscal sustainability are provided, as well as exemplifications of policy implementations in numerous countries. The paper also presents some of the challenges in maintaining fiscal soundness in the context of Thailand. It is shown that as a result of favorable conditions, Thailand’s fiscal stance remains robust. However, the country is facing several medium-term challenges. In addition, as fiscal unsustainability could bring about economic instability, market participants should closely monitor the actions of the government; hence, fiscal sustainability can be assessed through the expectations or perceptions of agents as represented by various indices. This paper provides various perspectives from various sectors as alternative approaches to determine fiscal soundness in Thailand